2023
DOI: 10.1038/s41598-022-21726-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microvesicles correlate with radiation proctitis complication after radiotherapy

Abstract: In a large retrospective study, we assessed the putative use of circulating microvesicles (MVs), as innovative biomarkers of radiation toxicity in a cohort of 208 patients with prostate adenocarcinoma overexposed to radiation. The level of platelet (P)-, monocyte (M)- and endothelial (E)-derived MVs were assessed by flow cytometry. Rectal bleeding toxicity scores were collected at the time of blood sampling and during the routine follow-up and were tested for association with MVs using a multivariate logistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…While a few studies have reported image-based predictors for proctitis and cystitis [4,14,17,18,23], the combination of different feature types has been explored infrequently [24,25]. In this study, we propose a scheme for predicting rectal and bladder toxicity using a combination of clinical, dosimetric, and radiomics features extracted from pretreatment planning computed tomography (CT) and magnetic resonance imaging (MRI) in rectal cancer patients.…”
Section: The Current Studymentioning
confidence: 99%
“…While a few studies have reported image-based predictors for proctitis and cystitis [4,14,17,18,23], the combination of different feature types has been explored infrequently [24,25]. In this study, we propose a scheme for predicting rectal and bladder toxicity using a combination of clinical, dosimetric, and radiomics features extracted from pretreatment planning computed tomography (CT) and magnetic resonance imaging (MRI) in rectal cancer patients.…”
Section: The Current Studymentioning
confidence: 99%